Surviving a crisis: A multilevel model of leadership styles, employees’ psychological capital and organizational resilience - Faith Njaramba; John Olukuru (PLoS ONE, 2025)
Building on the emerging research on organizational resilience in crisis, we tested a model of transformational and directive leadership styles and their association with organizational resilience in a crisis via employees’ psychological capital. Three hundred and one small and medium sized enterprises in Kenya provided usable survey data. The hypotheses were tested using multilevel structural equation modelling (MSEM) technique. The results show that both transformational and directive leadership styles were significant and positive predictors of organizational resilience through the mediating role of employees’ psychological capital. From a practical perspective, as SMEs struggle to be resilient during crises, leaders should adopt effective leadership styles such as transformational and directive and also consider their employees’ psychological experience of a crisis.